Designing a Reminders System in Highly Automated Vehicles’ Interfaces for Individuals With Mild Cognitive Impairment - Eskandar, Mahtab; Giang, Wayne C. W.; Motamedi, Sanaz; Devos, Hannes; Koon, Lyndsie; Akinwuntan, Abiodun; Kondyli, Alexandra (Frontiers in Future Transportation, 2022)
Many individuals with mild cognitive impairment (MCI) struggle with the decision to cease driving prematurely due to cognitive deficiencies in processing speed, memory, attention, judgment, or visuospatial skills. Highly automated vehicles (AVs) can be used as assistive technologies for individuals with MCI, performing all driving tasks for them, and extending their safe and independent mobility. However, use of AVs introduces a different set of challenges than manual driving. These challenges rely more heavily on memory and decision-making abilities of its users. Therefore, the goal of this study is to investigate the challenges that individuals with MCI might face with respect to interacting with highly AVs and to use that knowledge to identify the design requirements for AVs’ in-vehicle interfaces. To achieve this goal, we conducted individual interviews with experts in driving rehabilitation, rehabilitation professionals, and academics with a focus on assistive technologies, rehabilitation sciences, engineering, and inclusive design (N=7). The thematic analysis of the data from these subject matter experts highlighted the necessity for reminders, defined as system-initiated prompts that assist individuals with remembering or acknowledging a specific piece of information, to be incorporated into highly AVs’ in-vehicle interfaces. We adopted a user-centered design process including information architecture, visual design, and interaction design to generate a reminders system that provides a system-initiated textual, visual, or auditory prompts and notifications to assist individuals with MCI with maintaining awareness of their current tasks and goals. The reminders system was designed to be displayed on a central dashboard display placed in front of the passenger’s seat and present important information that address the users’ difficulties with prospective memory, remembering and understanding the features of the highly AV, and understanding the current trip status. This study serves as an initial investigation into ensuring that the experience of using highly AVs is inclusive and can support the needs of individuals with MCI. The designed interactions proposed by the reminders system can serve as a platform for future in-vehicle interfaces.